KULIT SALAK ( SALACA ZALACCA) ANTI DIABETES T2: Insights from a Comprehensive Review of the Literature - Ayu Suntara, Ditte; M. Hutapea, Albert (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Type 2 Diabetes Mellitus (T2DM) is a complex and multifactorial disease, which causes metabolic disorders to the point of insulin resistance in peripheral tissues (Heidyana, 2020). Diabetes Mellitus (DM) is a condition when the body is unable to convert food into energy as it should. With the development of science, there are many new discoveries that direct diabetes treatment using functional foods and changing lifestyle, one of which is herbs. One herb that can control blood sugar levels is using the herb bark of snake fruit (Salacca Zalacca). Aim, Analyzing Salak Fruit Skin (Salacca Zalacca) as an Anti-Diabetic T2. Literature Review Design, Data source: Search using the Google Chrome database, Google Scholar, articles on the topic published in Indonesian and English from 2018-2023. Review Method: Search for articles using keywords that match the writing. Articles are selected by journal selection, abstract selection with inclusion and exclusion criteria so that journals are found that can be reviewed. The results of the literature review of the 8 selected articles were then categorized into 2 characteristics of salak fruit skin. Consisting of 2 articles on compounds in salak fruit skin (Joshua & Sinuraya, 2018), (Setyawaty et al., 2020). And 6 articles about salak fruit peel as anti-diabetic (Dhyanaputri et al., 2016), (Ghofur et al., 2020), (Anggraeni & Nasution, 2019), (Sholihah & Tarmidzi, 2022), and (Handayani et al. , 2021). Overall conclusion: Salak fruit skin is one of the herbal plants that has antidiabetic effects. This is supported by the many compounds contained in snake fruit skin which can treat diabetes. Salak peel plays a role in lowering blood sugar levels, inhibiting α-glucosidase, regenerating pancreatic β-cells and increasing insulin sensitivity. Keywords: snake fruit peel (Salacca Zalacca), blood glucose levels, Diabetes Mellitus Type 2, herbs, Literature Review